Membangun Kampus Toleran: Solusi Pencegahan Radikalisme melalui Pendidikan Kritis dan Dialog Terbuka dalam Perspektif Islam - Cici Sari Puspita Dewi; Delima Widi Astuti; Najmina Nasywa Syamila; Muhamad Parhan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Education plays a very important role in shaping an individual’s character and mindset, including in preventing radicalism. With education, it is hoped that a person can develop themselves and bring positive change to the nation and state, so that education becomes a life guide reflected in every activity undertaken. The research method used this time is a qualitative research method with a descriptive approach. This method was chosen because it aims to systematically describe facts or characteristics factually and accurately. This study presents data as it is without manipulation or other additional treatments. From an Islamic perspective, the values of tolerance, dialogue, and justice are important foundations in building a harmonious society. This research found that the integration of moderate Islamic values into the curriculum and campus activities can strengthen efforts to prevent radicalism. Radicalism on campus is a phenomenon that needs to be watched out for because it can threaten the values of tolerance, diversity, and national unity. Critical education not only provides space for students to think analytically and reflectively, but also equips them with social awareness. Building a campus free from radicalism is not only the responsibility of educational institutions, but also requires the active involvement of all campus elements, through strong collaboration between students, lecturers, as well as strengthening the values of moderation and inclusivity.